2023
DOI: 10.1039/d3nr02396f
|View full text |Cite
|
Sign up to set email alerts
|

Immunochromatographic enhancement strategy for SARS-CoV-2 detection based on nanotechnology

Qingwen Sun,
Qihong Ning,
Tangan Li
et al.

Abstract: This review summarizes new methods for improving the sensitivity of immunochromatographic SARS-CoV-2 detection based on nanotechnology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 127 publications
0
1
0
Order By: Relevance
“…It has been reported that some commercially available rapid antigen detection kits are 10 2 -10 5 times less sensitive than RT-PCR [27][28][29]. Great efforts have been made to enhance the sensitivity of LFIA for detecting SARS-CoV-2 [30]. For example, Ruantip et al incorporated an enhancement pad to a conventional LFIA and achieved a 10-fold improvement in sensitivity (i.e., 0.5 ng/mL N protein) [31].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that some commercially available rapid antigen detection kits are 10 2 -10 5 times less sensitive than RT-PCR [27][28][29]. Great efforts have been made to enhance the sensitivity of LFIA for detecting SARS-CoV-2 [30]. For example, Ruantip et al incorporated an enhancement pad to a conventional LFIA and achieved a 10-fold improvement in sensitivity (i.e., 0.5 ng/mL N protein) [31].…”
Section: Discussionmentioning
confidence: 99%